Combined effects of double mutations on catalytic activity and structural stability contribute to clinical manifestations of glucose-6-phosphate dehydrogenase deficiency - Phonchanan Pakparnich; Sirapapha Sudsumrit; Mallika Imwong; Teeraporn Suteewong; Kamonwan Chamchoy; Danaya Pakotiprapha; Ubolsree Leartsakulpanich; Usa Boonyuen (Scientific Reports, 2021)
Abstract Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzymopathy in humans, affecting ~ 500 million worldwide. A detailed study of the structural stability and catalytic activity of G6PD variants is required to understand how different mutations cause varying degrees of enzyme deficiency, reflecting the response of G6PD variants to oxidative stress. Furthermore, for G6PD double variants, investigating how two mutations jointly cause severe enzyme deficiency is important. Here, we characterized the functional and structural properties of nine G6PD variants: G6PD Gaohe, G6PD Mahidol, G6PD Shoklo, G6PD Canton, G6PD Kaiping, G6PD Gaohe + Kaiping, G6PD Mahidol + Canton, G6PD Mahidol + Kaiping and G6PD Canton + Kaiping. All variants were less catalytically active and structurally stable than the wild type enzyme, with G6PD double mutations having a greater impact than single mutations. G6PD Shoklo and G6PD Canton + Kaiping were the least catalytically active single and double variants, respectively. The combined effects of two mutations were observed, with the Canton mutation reducing structural stability and the Kaiping mutation increasing it in the double mutations. Severe enzyme deficiency in the double mutants was mainly determined by the trade-off between protein stability and catalytic activity. Additionally, it was demonstrated that AG1, a G6PD activator, only marginally increased G6PD enzymatic activity and stability.
Keywords: Neonatal Health and Biochemistry; Methemoglobinemia and Tumor Lysis Syndrome